Pengaruh Variasi Waktu Sintering Terhadap Pertumbuhan Fase Bahan Superkonduktor BSCCO-2212 dengan Kadar Ca=1,10 Menggunakan Metode Pencampuran Basah - Karlina Rahmah; Suprihatin Suprihatin; Pulung Karo Karo (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2020)
This research was conducted to determine the effect of sintering time on the formation of the superconducting phase BSCCO-2212 by calculating the level of purity of the phases formed and looking at the microstructure. The variation of sintering time was 10, 20, 30 and 40 hours using the wet mixing method. The sample was calcinated with 800 °C for 10 hours and sintered with 830 °C. The XRD’s characterization result shows a decrease in phase purity with increasing the sintering time. The relative high volume fraction of the BSCCO-2212/ts10 sample is 90,48% while, the lowest volume fraction of BSCCO-2212/tc40 is 50,74%. The relative high orientation degree of BSCCO-2212/ts20 is 18,47% and the lowest orientation degree of BSCCO-2212/ts10 is 8,4%. The SEM’s characterization result shows of all samples have been oriented and have relatively little space between slabs (voids).